Digital Recordkeeping Checklist: Digital Recordkeeping Self-Assessment Checklist/ Digital Belge Yönetimi: Dijital Belgelerin Üretimi, Yönetimi ve Korunması için Rehber Australia: National Archives of Australia, 2004 ISBN 1-920807-08-X. - (:unkn) unknown (My University, 2006)
0

The book provides comprehensive help to Australian Government agencies in creating, managing and preserving their digital records. It will assist staff responsible for digital records and information to manage digital records for as long as they are required. This publication has a companion. The Digital Recordkeeping Checklist is a self-assessment tool for Australian Government agencies to evaluate their management of digital records. In November 2004, two Australian Government agencies– IP Australia and the Royal Australian Mint–reviewed their recordkeeping systems using the guidelines and checklist. The outcomes of these audits are documented in case studies attached to Archives Advice 65. The case studies show how the guidelines and checklist can help agencies review their recordkeeping systems and prioritise areas for improvement.
Keywords: Bilgi, Belge Yönetimi